Energy Cost Saving and Economic Prospective of China Pakistan Economic Corridor - Idrees, Rao Qasim; Shapiee, Rohimi; Ahamat, Haniff (International Journal of Energy Economics and Policy, 2018)
The China Pakistan Economic Corridor (CPEC) is a landmark project in the history of Pakistan. It is the largest investment Pakistan has ever attracted since independence and largest by China in any foreign country. This research article examines the energy cost saving and trade prospective in terms of shortest trade route for China and toll income generated through this transit corridor for Pakistan. The first part of the article discusses the prospective advantages for China while transporting oil and doing trade with Middle East and North Africa under CPEC route. Second part highlights the estimated toll income which Pakistan can get through the use of CPEC trade routes from Khunjrab to Gwadar Sea port. Third part provides analytical study among current and prospective CPEC trading route and shipping cost between China and Middle East. Finally, this study provides recommendations for the ultimate success of CPEC transit trade and mutual benefits of Pakistan and China. This study further reveals and concludes that China through CPEC has tremendous opportunity to lowering energy cost and gets shortest route for trade with Middle East and Africa; hence China can reduce transit time and shipping cost significantly, while Pakistan can generate revenue about thrice of its current budget from toll taxes income. Keywords: China Pakistan Economic Corridor, low energy cost, toll income JEL Classifications: Q43, Q52 DOI: https://doi.org/10.32479/ijeep.6713